In-silico screening and in-vitro assay show the antiviral effect of Indomethacin against SARS-CoV-2. (August 2022) - Chakraborty, Rajkumar; Bhattacharje, Gourab; Baral, Joydeep; Manna, Bharat; Mullick, Jayati; Mathapati, Basavaraj S.; Abraham, Priya; J, Madhumathi; Hasija, Yasha; Ghosh, Amit; Das, Amit Kumar
Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has caused the worldwide spread of coronavirus disease 19 (COVID-19), and till now, it has caused death to more than 6.2 million people. Although various vaccines and drug candidates are being tested globally with limited to moderate success, a comprehensive therapeutic cure is yet to be achieved. In this study, we applied computational drug repurposing methods complemented with the analyses of the already existing gene expression data to find better therapeutics in treatment and recovery. Primarily, we identified the most crucial proteins of SARS-CoV-2 and host human cells responsible for viral infection and host response. An in-silico screening of the existing drugs was performed against the crucial proteins for SARS-CoV-2 infection, and a few existing drugs were shortlisted. Further, we analyzed the gene expression data of SARS-CoV-2 in human lung epithelial cells and investigated the molecules that can reverse the cellular mRNA expression profiles in the diseased state. LINCS L1000 and Comparative Toxicogenomics Database (CTD) were utilized to obtain two sets of compounds that can be used to counter SARS-CoV-2 infection from the gene expression perspective. Indomethacin, a nonsteroidal anti-inflammatory drug (NSAID), and Vitamin-A were found in two sets of compounds, and in the in-silico screening of existing drugs to treat SARS-CoV-2. Our in-silico findings on Indomethacin were further successfully validated by in-vitro testing in Vero CCL-81 cells with an IC50 of 12 μM. Along with these findings, we briefly discuss the possible roles of Indomethacin and Vitamin-A to counter the SARS-CoV-2 infection in humans. Highlights: Crucial host and viral proteins involved in SARS-CoV-2 infection were selected. Drug repurposing study was conducted against the crucial proteins. To reverse genetic changes incurred by Covid19 gene expression data were studied. Above analyses suggested Vitamin A and Indomethacin may be used against SARS-CoV-2 infection. Indomethacin exhibited antiviral activity against SARS-CoV-2 in vitro.